Health, biodiversity, and natural resource use on the Amazon frontier: an ecosystem approach - Murray Tamsyn P.; Sánchez-Choy José (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2001)
This study aims to improve the health of rural Amazonian communities through the development and application of a participatory ecosystem approach to human health assessment. In the study area marked seasonal fluctuations dictate food availability, water quality and disease outbreak. Determining the causal linkages between ecosystem variables, resource use and health required a variety of forms of inquiry at multiple scales with local participation. Landscape spatial mapping of resource use demonstrated the diversity of the ecological resources upon which communities depend. Household surveys detailed family and individual consumption and production patterns. Anthropometric measurements, parasite loading, water quality and anemia levels were used as indicators of health status. This was complemented with an ethnographic and participatory health assessment that provided the foundation for developing community action plans addressing health issues. Discussion is focused on three attributes of an ecosystem approach; (a) methodological pluralism, (b) cross-scale interactions and (c) participatory action research.